Diabetic retinopathy and chronic kidney disease: associations and comorbidities in a large diabetic population: the Tongren health care study - Gao, Li Qin; Xue, Can Can; Cui, Jing; Xu, Jie; Zhang, Chun; Chen, Dong Ning; Jonas, Jost B.; Wang, Ya Xing (American journal of nephrology, 2023)
Introduction: The aim of the study was to investigate associations between diabetic retinopathy (DR) and chronic kidney disease (CKD) in patients with type 2 diabetes (TD2). Methods: The participants of the cross-sectional, community-based Tongren Health Care Study underwent a detailed medical and ophthalmological examination. We defined TD2 by a fasting plasma glucose concentration of ≥7.0 mmol/L or a medical history. CKD was classified as either reduced estimated glomerular filtration rate (eGFR) of <60 mL/min/1.73 mm2 or presence of albuminuria. DR was assessed using color fundus photographs. Results: Out of 62,217 participants of the Tongren Health Care Study, 5,103 (8.2%) patients had TD2. The prevalence of DR was 12.8% (95% CI, 11.8%, 13.7%), CKD was 13.3% (95% CI, 12.4%, 14.3%), and the subtypes of CKD including reduced eGFR and albuminuria was 4.6% (95% CI, 4.2%, 5.1%) and 10.1% (95% CI, 9.3%, 10.9%), respectively. DR was detectable in 21.0% of the patients with CKD, while CKD was present in 20.9% of the DR patients. Higher DR prevalence was associated with higher prevalence of albuminuria and reduced eGFR (both p < 0.05). Factors independently associated with the presence of CKD instead of DR were older age (p < 0.001, OR = 1.05), a higher body mass index (p < 0.001, OR = 1.14), a higher serum concentration of triglycerides (p < 0.001, OR = 1.26), and a lower blood glucose (p < 0.001, OR = 0.93). Having hypertension was additionally associated with the presence of reduced eGFR as compared with DR (p = 0.005, OR = 4.47). Conclusions: TD2 patients of older age and with higher body mass index, hypertension, and dyslipidemia had a higher probability of being affected by CKD rather than DR, while those with a higher blood glucose level were more prone to DR than CKD.
Gesehen am 29.02.2024